Global Analysis of CPEBs Reveals Sequential and Non-Redundant Functions in Mitotic Cell Cycle - Giangarrà, Valeria (PLoS One, 2015)
CPEB (Cytoplasmic Polyadenylation Element Binding) proteins are a family of four RNA-binding proteins that regulate the translation of maternal mRNAs controlling meiotic cell cycle progression. But CPEBs are not limited to the transcriptionally silent germline; they are also expressed, in various combinations, in somatic cells, yet their role in regulation of mitosis-related gene expression is largely unknown. Deregulation of CPEB1 and CPEB4 have been linked to tumor development. However, a systematic analysis addressing their requirements for the temporal regulation of mitotic gene expression has yet to be performed. This study addresses the requirements of each of the four CPEBs for mitotic phase transitions, with a particular focus on cytoplasmic polyadenylation and translational regulation. We demonstrate that CPEB3 is the only member dispensable for mitotic cell division, whereas the other three members, CPEB1, 2, and 4, are essential to successful mitotic cell division. Thus, CPEB1 is required for prophase entry, CPEB2 for metaphase and CPEB4 for cytokinesis. These three CPEBs have sequential non-redundant functions that promote the phase-specific polyadenylation and translational activation of CPE-regulated transcripts in the mitotic cell cycle.